Treasure island - Brook, Henry; McNee, Ian (Usborne Publishing Ltd London, 2013)
Robert Louis Stevenson's gripping tale of pirates and adventure, retold for today's readers, is as exciting as when it was written. Young Jim Hawkins discovers a treasure map and sets sail on a voyage that will change his life forever